MULTIMODAL ASPECTS OF CONGRATULATORY AND WISH SPEECH ACTS IN MODERN COMMUNICATION - Kurbanova Gulshodakhon (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Congratulations and wishes are everyday expressions that are used in all languages. This article examines the differences between the multimodal aspects of speech acts according to Searle's theories and finds that Uzbek expressions are generally longer and more emotional. In comparison, English expressions are shorter and more direct. However, in digital communication, both languages show similar patterns due to the use of emojis and informal style. The study concludes that speech act theory should be adapted to modern communication, where language is not only verbal but also multimodal.